Exploring the management competencies of nurse managers in the Greater Accra Region, Ghana - Adelaide Maria Ansah Ofei; Yennuten Paarima; Theresa Barnes (Elsevier, 2020)
Introduction: Nurse managers (NMs) have a multifaceted role in translating organizational strategic vision, values, and objectives into action at the unit level. NMs do not only provide administrative and clinical leadership but have 24-h responsibility for all patient care services in the unit. Even though there is a paucity of literature on management competencies, NMs need to effectively and efficiently discharge their management roles. Using the Katz model as the organizing framework, this study examined important management competencies significant for healthcare delivery. Methods: A quantitative exploratory design was used to collect data from 522 nurses in 19 hospitals in the Greater Accra region. Data were analyzed using descriptive statistics. Results: The findings revealed that NMs possessed all the management competencies of the Katz model. NMs exhibited moderate level of management competencies (mean = 3.47, SD = 0.97); technical skill was the highest scored (mean = 3.56, SD = 0.96), followed by conceptual skill (mean = 3.50, SD = 0.98) and human relationship skill (mean = 3.34, SD = 0.99). Conclusion: NMs have been identified as critical stakeholders in addressing healthcare challenges therefore, it is imperative to equip them with the relevant skills to enable them to manage these challenges in order to enhance and enable effective, efficient, and responsive healthcare systems. The study identified technical, human, and conceptual skills to be essential for nursing management in Ghana. This study is timely as the Ghana Health Service aims at strengthening the leadership and governance capacity of the health workforce.